PERSEPSI GURU TENTANG KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SD MUHAMMADIYAH SE KOTA BANDAR LAMPUNG - Dinda Permata Sari; Muhammad Akmansyah; Achi Rinaldi (MANAGERE : Indonesian Journal of Educational Management, 2021)
The focus of this study was to determine the effect of teacher perceptions about the principal's managerial ability and work motivation on the performance of teachers at Muhammadiyah Elementary School in Bandar Lampung City. This research uses associative quantitative research with a total population of 123 teachers and a sample of 94 teachers. The data collection technique used a questionnaire. The data were analyzed using simple linear regression analysis and multiple linear regression analysis. The results showed that the effect of teacher perceptions about the principal's managerial ability and work motivation on teacher performance was 54.9% while the remaining 45.1% was influenced by other factors. So it can be concluded that the better the teacher's perception of the principal's managerial ability and work motivation, the higher the teacher's performance.